ChemInform Abstract: Synthesis of Indoles by Palladium‐Catalyzed Reductive Cyclization of β‐Nitrostyrenes with Carbon Monoxide as the Reductant. Issue 3 (29th December 2015) - Ferretti, Francesco; EL‐Atawy, Mohamed A.; Muto, Stefania; Hagar, Mohamed; Gallo, Emma; Ragaini, Fabio
Abstract: The optimized conditions are applied to the preparation of a series of 2‐ or 3‐substituted indole structures bearing additional functions at the arene part.